Approximation of math model of the combined cutting soil`s critical depth with influence of working speed - Kravets, Sviatoslav; Zoria, Roman (КНУБА, 2017)
The purpose is approximation of mathematical model of processes of cutting and loosening of the soil for the receipt of analytical dependence of determination of critical depth of loosening taking into account the working speed at the combined tiered destruction of soil. An approximation based on regression analysis used in the processing of data derived from experiments with a number of parallel observations in the experiment. Built graph of the dependency between relative critical depth, working speed of the working body and angle cutting soil. Identify the value of critical depth loosening for five types of soil and full range of working speeds, depending on the physical and mechanical properties of the soil.
Keywords: angle cutting; depth loosening; operating speed; critical depth; free cutting; blocked cutting; combined cutting; 624.132.3